Eigenvalues and Eigenfunctions of a Schrödinger Operator Associated with a Finite Combination of Dirac-Delta Functions and CH Peakons (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we first study the Schrödinger operators with the following weighted function $\sum\limits_{i=1}^n p_i δ(x - a_i)$, which is actually a finite linear combination of Dirac-Delta functions, and then discuss the same operator equipped with the same kind of potential function. With the aid of the boundary conditions, all possible eigenvalues and eigenfunctions of the self-adjoint Schrödinger operator are investigated. Furthermore, as a practical application, the spectrum distribution of such a Dirac-Delta type Schrödinger operator either weighted or potential is well applied to the remarkable integrable Camassa-Holm (CH) equation.
Keywords: Schrödinger operator; Boundary conditions; Soliton; Peakon solution; Cammassa-Holm equation.